Management factors that impact employees in rural veterinary practices - Gilliam, Gabryelle Nicole (Kansas State University, 2020)
Recognizing the various ways different management factors can impact employees in rural veterinary practices is important for the success and wellbeing of both the employees and the practice. Three studies were conducted to evaluate any potential associations business management factors could have on rural veterinary practices. The first study evaluated overall job and career satisfaction, as well as, financial, physical, and emotional health of veterinarians. Most respondents were satisfied with their job (83.0%) and career (84.1%); both job and career satisfaction were higher when respondents believed they received adequate recognition. Health outcomes were found to be impacted by financial factors, staffing numbers, and receiving adequate recognition. The second study identified associations among administrative personnel and veterinarian turnover and compensation packages. Lower administrative personnel turnover was associated with the presence of veterinarian retirement plans, asset protection plans, new associate compensation packages, and the number of veterinarians leaving the practice. Lower veterinarian turnover was associated with veterinarian ownership and the number of administrative personnel leaving the practice. Higher owner compensation packages were associated with longer practice establishment, use of marketing plans, and more veterinarian annual vacation days. Higher compensation packages for new associates were associated with more administrative personnel, use of marketing plans, more all-staff meetings, more veterinarian annual vacation days, and more hiring of administrative personnel. Higher compensation packages for 10-year associates were associated with more administrative personnel, more all-veterinarian and all-staff meetings, fewer veterinarian hours per week, more hiring of administrative personnel, and fewer administrative personnel leaving the practice. The third study determined the perceived presence of gender bias from both clients and employers, and during the hiring process in regards to the number of applications submitted and interviews conducted. The graduation year was found to be significantly associated with the perception of gender bias from current clients, and this effect was modified by gender. Regarding the perception of gender bias from clients in the first year of practice, graduation year and gender were both significantly associated. The perceived presence of gender bias from employers in the first year of practice was found to be significantly associated with gender. The number of applications submitted for one first position was associated with graduation year, gender, and being the first of your gender at the practice. The number of interviews received for one’s first position was significantly associated with graduation year. Many management strategies were evaluated during these studies. Understanding how these strategies impact employees can influence satisfaction, health, retention, compensation, and equality in rural practices.
Keywords: veterinary turnover; practice management; employee compensation; gender bias